Simple Project-Based learning to Improve Grammar Element in Teaching Speaking - Muhammad Husnu; Ahmad Yusri; Muhamad Ridwan; Suhaeli Robbi Awaludin (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This paper aims to show the Simple project-based learning in Teaching speaking, success. English and student attention using techniques during the learning process. quantitative data Experimentally conducted and collected using pre-study, treatment, and post-study techniques Offer multiple-choice tests before and after applying the technique. Although the data are qualitative, Utilize surveys by distributing surveys to students and teacher also conducting multiple related interviews to simple project-based learning. Only test results before applying the technique 65% of the students are proficient in speaking English, but after demonstrating The technique, it improved the student's English speaking ability to 89%. On the other hand, student analysis Studies have also shown the Simple project-based learning in Teaching Speaking techniques are effective to Improve the students' English skills. Application of Simple project-based learning Techniques in Learning For this reason, improving your English, especially your speaking skills, is the right strategy to improve your students' skills. Techniques can turn abstract concepts into reality in the classroom.